DEVELOPING EMOTION REGULATION SKILLS BY EMOTION REGULATION SKILLS SYSTEM TRAINING FOR CHILDREN WITH MILD INTELLECTUAL DISABILITY - Efika Fiona; Wahyu Indianti (JURNAL PSIKOLOGI INSIGHT, 2018)
Intellectual disability is deficits in intellectual functions, adaptive functions, and these deficits occure during the developmental period (before the age of eighteen). Emotion regulation related to the functions and become the problems for children with mild intellectual disability. Emotion regulation is individual’s ability to refrain himself from improper behavior concerning negative and positive emotions that he feels, to manage himself so that he does not depend on his mood condition, to calm down himself when strong emotion arises, and to focus his attention when strong emotion appears. Emotion regulation is extremely needed for adaptation in maintaining relations with other people. The one of interventions that can be used to handle emotion regulation problem for children with intellectual disability is by giving emotion regulation skills system training. This research uses single subject design. The result of this research shows that emotion regulation skills system training gives positive impacts on cognitive and behavior aspects of the subject. The application of these skills in daily life is related to the roles of people around the subject who can understand how to apply the skills and remind the subject